Characterization, Electrical and Magnetic Properties of Nd2Zr2O7 Compound - Raghuvanshi, Pooja; Thakur, A.N.; Rani, Priyanka (Asian Journal of Chemistry, 2013)
The Nd2Zr2O7 compound is prepared by using solid state reaction technique. Its structural and electrical properties have been investigated. X-ray diffraction pattern indicates that Nd2Zr2O7 crystallizes in an orthorhombic pervoskite structure. The compound was characterized through powder differential thermal analysis, thermogravimetric analysis and derivative thermogravimetry. The electrical conductivity (s), dielectric constant (e'), dielectric loss (e'') and quality factor (Q) of Nd2Zr2O7 was measured in the temperature range 300-1125K at an internal frequency of 1 kHz. The log s vs. 103/T plot yield two different slopes separated by break temperature (T1). The activation energy below and above T1 have been estimated as 0.13 eV and 2.1 eV respectively. Hence the electrical conductivity below T1 is essentially extrinsic always associated with impurities, defects and interstitials and conductivity above T1 is essentially intrinsic due to the change in conduction mechanism. The magnetic susceptibility of the compound was measured in the temperature range 300-1100 K at field 1.55 × 10-1 Tesla. The magnetism in this compound arises from the rare-earth ions, while Zr is non magnetic.